2014
DOI: 10.2147/shtt.s42673
|View full text |Cite
|
Sign up to set email alerts
|

Homecare user needs from the perspective of the patient and carers: a review

Abstract: There is a global shift towards a blending of care delivery within formal and informal environments in direct response to economic and demographic pressures. Homecare is at the hub of this activity, enabling people to age in place and keeping families intact. However, our understanding of patient and carer needs is fragmented; understandably so, given the complexity of these needs. This descriptive review offers a content analysis of papers focused on patients' and carers' needs and homecare published between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 169 publications
(242 reference statements)
0
22
0
Order By: Relevance
“…After the information meetings, 11 people signed up for participation in the study: three leaders to in-depth interviews and eight home care staff members to focus group interviews. 2 The three leaders agreed to participate during the meeting, while the home care staff who wanted to participate gave notice to their leader shortly after. All who wanted to participate in the study were included.…”
Section: Participantsmentioning
confidence: 99%
“…After the information meetings, 11 people signed up for participation in the study: three leaders to in-depth interviews and eight home care staff members to focus group interviews. 2 The three leaders agreed to participate during the meeting, while the home care staff who wanted to participate gave notice to their leader shortly after. All who wanted to participate in the study were included.…”
Section: Participantsmentioning
confidence: 99%
“…However, these results were based on data collected over 14 years ago, and it is unclear if they are still valid today. Social needs were nonetheless identified in a more recent review about patients' and care partners' needs (Keeling, ). Furthermore, Keeling () emphasised the necessity of information sharing, emotional support and collaboration among the stakeholders (home care services, care partners and care receivers), yet argued that the best way to achieve such collaboration was still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Social needs were nonetheless identified in a more recent review about patients' and care partners' needs (Keeling, ). Furthermore, Keeling () emphasised the necessity of information sharing, emotional support and collaboration among the stakeholders (home care services, care partners and care receivers), yet argued that the best way to achieve such collaboration was still unknown. The review (Keeling, ) addressed all age groups, but the search was restricted to one database (Medline) and studies conducted from 2010–2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When analyzing instruments for the assessment of patients receiving home care in other countries as well as in Brazilian trial runs (14)(15)(16)(17)(18)(19)(20) , the authors found considerable diversity of models and organizations in home care in the last few years, in addition to various study designs and sample characteristics. However, this analysis does not give a complete understanding of the main aspects of home care in those countries and in those services, especially public HC services, that are defined mainly by their humanized and inclusive nature, with user-centered care plans and multidisciplinary health teams.…”
Section: Introductionmentioning
confidence: 99%